Tanggung Gugat Terhadap Kerugian Yang Diterbitkan oleh Anak di Sekolah Berdasarkan Pasal 1367 KUHPerdata: Tanggung Gungat, Kerugian, Pasal 1367 KUHPerdata. - Darmiwati Darmiwati2021 (JURNAL HUKUM DAS SOLLEN, 2021)
Schools as institutions that provide formal education play a very important role in producing quality generations, both cognitively and effectively. In school life, students do not rule out dealing with legal problems because of the harmful actions they do inside and outside school. detrimental acts are regulated in Article 1365 of the Civil Code which reads that "every act that violates the law and brings harm to others, obliges the person who caused the loss because of his mistake to replace the loss. Such detrimental actions must be accounted for in accordance with applicable legal provisions. Accountability in the Civil Code is not only for one's own mistakes, but also for mistakes made by others with certain provisions. As the provisions in Article 1367 paragraph (1) of the Civil Code which reads that "A person is not only responsible for losses caused by his own actions, but also for losses caused by the actions of people who are his dependents or caused by goods that are under his control. . In general, if there is an unlawful act published by a student at school, either intentionally or unintentionally, the parents are responsible for the act. This is what the research wants to examine by connecting the existing cases.